Zambia : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance (TA) report focuses on four key work areas which may lead to improvement of Government Finance Statistics (GFS) for fiscal analysis, support policy making decisions in Zambia, and improve African Department surveillance. The mission found out that the Coordinating Committee, recommended in the previous TA mission, was not yet established. The mission reviewed progress on the legal and institutional arrangements supporting the compilation of GFS as a follow up from recommendations of the previous GFS TA mission and found that the legislation reforms were on track, especially regarding the Public Finance Act. The report also found that Central Statistical Office (CSO) is working on the revision of the Statistics Act to follow the new strategy for National Development of Statistics. For sustainability and consistency purposes, the mission recommended that the CSO staff produce a GFS manual for compilation and dissemination of GFS data.